URGENSI METODOLOGIS PENGKAJIAN ISLAM - Tasbih, Tasbih (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
The main problem in this paper is how the methodological description of Islamic studies? The subject matter is elaborated into two sub-problems namely: what is the position of Islam as the object of study and what is the scope of Islamic study? The aim is to determine the position of Islam as an object of study and the scope of Islamic studies. The purpose is to introduce and photograph Islam as a whole. The results show that Islam as an object of study must be understood and approached with at least three approaches; namely the traditional approach, rational approach and mystical approach. The scope of Islamic studies can be expanded even further through historical, theological, spiritual, legal and social studies studies. The implication of this research is that Islam is open to be examined from various aspects other than those mentioned in this paper.